Evaluation of the own body in women with current and remitted borderline personality disorder: evidence for long-lasting effects of childhood sexual abuse - Kleindienst, Nikolaus; Löffler, Annette; Herzig, Madeleine; Bertsch, Katja; Bekrater-Bodmann, Robin (European journal of psychotraumatology, 2020)
Background Evaluation of one's own body highly depends on psychopathology. In contrast to healthy women, body evaluation is negative in women from several diagnostic groups. Particularly negative ratings have been reported in disorders related to childhood sexual abuse (CSA) including borderline personality disorder (BPD). However, it is unknown whether this negative evaluation persists beyond symptomatic remission, whether it depends on the topography of body areas (sexually connoted versus neutral areas), and whether it depends on CSA. Objective First, we aimed at a quantitative comparison of body evaluation across three diagnostic groups: current BPD (cBPD), remitted BPD (rBPD), and healthy controls (HC). Second, we aimed at clarifying the potentially moderating role of a history of CSA and of the sexual connotation of body areas. Methods The study included 68 women from the diagnostic groups of interest (cBPD, rBPD, and HC). These diagnoses were established with the International Personality Disorder Examination. The participants used the Survey of Body Areas to quantify the evaluation of the own body and the Childhood Trauma Questionnaire for assessing CSA. Results While the evaluation of the own body was generally negative in women from the cBPD group it was positive in those who had remitted from BPD. However, their positive scores were strictly confined to neutral body areas, whereas the evaluation of sexually connoted body areas was negative, resembling the respective evaluation in cBPD patients and contrasting the positive evaluation of sexually connoted areas in healthy women. The negative evaluation of sexually connoted areas in remitted women was significantly related to a history of CSA. Conclusions Women with BPD may require a specifically designed intervention to achieve a positive evaluation of their entire body. The evaluation of sexually connoted body areas seems to remain an issue even after remission from the disorder has been achieved.
Gesehen am 06.08.2020